2014
DOI: 10.3390/ijms150712778
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin Down-Regulates Multiple Drug Resistant (MDR)/HIF-1α through Regulating AMPK/mTORC1 Signaling in GBC-SD Gallbladder Cancer Cells

Abstract: Gallbladder cancer is the most common malignancy of the bile duct, with low 5-year survival rate and poor prognosis. Novel effective treatments are urgently needed for the therapy of this disease. Here, we showed that cordycepin, the bioactive compound in genus Cordyceps, induced growth inhibition and apoptosis in cultured gallbladder cancer cells (Mz-ChA-1, QBC939 and GBC-SD lines). We found that cordycepin inhibited mTOR complex 1 (mTORC1) activation and down-regulated multiple drug resistant (MDR)/hypoxia-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 48 publications
0
50
0
1
Order By: Relevance
“…AMPK-mediated autophagy could be through direct mechanism (phosphorylation of Ulk1) and/or indirect mechanisms (mTORC1 inhibition) [61, 62]. Recent studies have confirmed that AMPK activation could lead to degradation of several oncogenic proteins or oncogenes [18, 19]. Further studies will be needed to explore the downstream effectors of AMPK that mediate MAGEA6 shRNA-induced inhibition of RCC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPK-mediated autophagy could be through direct mechanism (phosphorylation of Ulk1) and/or indirect mechanisms (mTORC1 inhibition) [61, 62]. Recent studies have confirmed that AMPK activation could lead to degradation of several oncogenic proteins or oncogenes [18, 19]. Further studies will be needed to explore the downstream effectors of AMPK that mediate MAGEA6 shRNA-induced inhibition of RCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also proposed AMPK as a key tumor suppressor protein [12-14]. Activated AMPK exerts anti-cancer functions via different mechanisms, including mTOR complex 1 (mTORC1) inhibition [15], autophagy induction [16], p53 activation [17], as well as degradation of several key oncogenic proteins [18, 19]. AMPK can also modulate epithelial-to-messenchymal transition (EMT) via regulating Akt-MDM2-Foxo3 signaling [20].…”
Section: Introductionmentioning
confidence: 99%
“…Multidrug resistance (MDR) is a main cause of breast cancer chemotherapy failure. 41 Hypoxia induces cellular adaptations which contribute to cancer progression and chemoresistance, with one of these adaptations being the expression of multidrug resistance proteins such as ABC transporters. 42 Evidence of MDR-1 or MRP1 upregulation through HIF-1 under hypoxia has recently been highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion was drawn that inhibition of cell proliferation and further apoptosis of SW480 and SW620 cells were induced by cordycepin [7]. Similar action of cordycepin was also demonstrated in gallbladder cancer cells in vitro with its additional effect in down regulation of multidrug resistance (MDR) expression [8]. Its mode of action was by activation of AMPK (adenosine monophosphate activated protein kinase) signaling which lead to degradation of MDR/ HIF-1α (hypoxia inducible factor), cordycepin also inhibited the mTORC1 (mammalian target of rapamycin complex 1) in gallbladder cancer cell which leads to loss of cancer cell viability and apoptosis.…”
Section: Effect Of Cs On Various Cancer Cellsmentioning
confidence: 76%